Study of polysaccharide gels at Prof. Nishinari's laboratory. (March 2023) - Nitta, Yoko
Abstract: Studies performed at Prof. Katsuyoshi Nishinari's laboratory are overviewed. The gelation and gel properties of gellan gum were investigated by rheological and thermal analyses. The change in the elastic modulus of gellan gum gels due to the temperature or immersion in salt solutions was interpreted from the model that Prof. Nishinari proposed. The fracture behavior of the large deformation of gellan gum gels was also explained by this model. The gel of xyloglucan from tamarind seed, in particular, a thermoreversible cold-setting gel that formed in the presence of epigallocatechin gallate or Na-type gellan, was studied. As examples of recent collaborative works with Prof. Nishinari, the gelation of β-glucan extracted from Sparassis crispa, an edible mushroom, and the application of sodium alginate and low methoxy pectin to rice noodles are also described. Graphical abstract: Image 1 Highlights: The reel chain model explained the elasticity of polysaccharide gels. Gel properties of gellan gum were interpreted by the reel chain model. Gelation of gellan gum, tamarind seed xyloglucan and β-glucan was studied. Gelation of alginate and low methoxy pectin was applied to texture modification.